Organic Metal Halide Hybrids: Bulk Assembly of Corrugated 1D Metal Halides with Broadband Yellow Emission (Advanced Optical Materials 6/2019). Issue 6 (19th March 2019) - Lin, Haoran; Zhou, Chenkun; Neu, Jennifer; Zhou, Yan; Han, Dan; Chen, Shiyou; Worku, Michael; Chaaban, Maya; Lee, Sujin; Berkwits, Ella; Siegrist, Theo; Du, Mao‐Hua; et al.
Abstract : The rich chemistry of organic metal halide hybrids has enabled the development of a variety of new functional materials with crystal structures beyond perovskites. In article number 1801474, Biwu Ma and co‐workers report a novel bulk assembly of one‐dimensional (1D) organic metal halide hybrid, C5 H16 N2 Pb2 Br6, in which lead bromide octahedrons form a corrugated chain structure via non‐planar edge‐sharing. This 1D material exhibits a broadband yellow emission peaked at 554 nm with a full width at half maximum of 155 nm with a photoluminescence quantum efficiency of around 10%, due to exciton self‐trapping.